Meningeal Metastasis Causing Chronic Subdural Hematoma in a Cancer Patient with Bilateral Papilledema and Suspected Cerebral Venous Thrombosis: A Case Report - Pangratz-Daller, Cornelia; Grimm, Jochen; Pfaff, Johannes A.R.; Kraus, Theo F.J.; Sotlar, Karl; Rahman Al-Schameri, Abdul; Kral, Michael; Griessenauer, Christoph J.; Schwartz, Christoph (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Meningeal metastasis has been reported as a very rare cause of chronic subdural hematoma (CSH). Here, we report a female patient who had undergone initial burr hole drainage of a CSH at an outside hospital. Postoperatively, the patient additionally suffered from visual impairment due to bilateral papilledema and the patient was eventually transferred to our neurosurgical department for additional treatment. A craniotomy was performed and due to intraoperative suspicious findings, histopathologic samples were obtained that revealed a metastasis of thus far undiagnosed triple negative breast cancer. Furthermore, the patient was suspected to have a partial cerebral venous thrombosis (CVT). Our case report addresses this extremely rare clinical constellation. We provide a detailed overview on our patient's clinical and radiologic course, and discuss the potential association of CSH with meningeal metastasis and bilateral papilledema.
Keywords: cerebral venous thrombosis; chronic subdural hematoma; magnetic resonance imaging; meningeal metastasis; papilledema